2021
DOI: 10.1186/s40168-021-01097-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the genetically obese (ob/ob) and diabetic (db/db) mice: two sides of the same coin

Abstract: Background Leptin-deficient ob/ob mice and leptin receptor-deficient db/db mice are commonly used mice models mimicking the conditions of obesity and type 2 diabetes development. However, although ob/ob and db/db mice are similarly gaining weight and developing massive obesity, db/db mice are more diabetic than ob/ob mice. It remains still unclear why targeting the same pathway—leptin signaling—leads to the development of two different phenotypes. Given that gut microbes dialogue with the host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 76 publications
7
102
0
1
Order By: Relevance
“…This finding may suggest that LEAP2 is overproduced by the ileum to counteract glucose intolerance induced by an HFHS diet or hyperphagia. Since the ileum of HFHS and of ob/ob and db/db mice presents with inter-related alterations in gut eCBome signaling (present results and [ 23 ]) and microbiota composition [ 23 , 42 , 43 ], we hypothesized a role of either system in the modulation of Leap2 expression. However, also, in this case, the only potential eCBome signaling pathway that changed in a manner similar to Leap2 expression following HFHS and in ob/ob and db/db mice was that mediated by PPARα and/or its ligands.…”
Section: Discussionmentioning
confidence: 90%
“…This finding may suggest that LEAP2 is overproduced by the ileum to counteract glucose intolerance induced by an HFHS diet or hyperphagia. Since the ileum of HFHS and of ob/ob and db/db mice presents with inter-related alterations in gut eCBome signaling (present results and [ 23 ]) and microbiota composition [ 23 , 42 , 43 ], we hypothesized a role of either system in the modulation of Leap2 expression. However, also, in this case, the only potential eCBome signaling pathway that changed in a manner similar to Leap2 expression following HFHS and in ob/ob and db/db mice was that mediated by PPARα and/or its ligands.…”
Section: Discussionmentioning
confidence: 90%
“…A high fat diet (HFD) promotes gut leakiness through dysbiosis, since antibiotic treatment has been shown to be effective in improving intestinal permeability and glucose homeostasis in HFD-fed mice [ 128 ]. However, in an experimental model of leptin-deficient mice, obesity per se was associated with increased intestinal permeability, due to reduced expression of occludin, ZO1, and mucin synthesis, regardless of diet [ 142 , 143 ].…”
Section: The Intestinal Barrier In Autoimmune Metabolic and Neurological Diseasesmentioning
confidence: 99%
“…Recent studies on mice with defective leptin pathways show how obese mutant mice are featured by major defects in bile acid synthesis and conjugation, together with higher expression of liver cholic acid [ 142 , 153 ].…”
Section: The Gut–liver Axismentioning
confidence: 99%
“…Recent data have shown that, along with CXCL5, circulating levels of CXCL1, with high affinity to CXCR2, are markedly increased in the db/db mice and correlate with obesity development [ 43 , 44 ]. KC, the human orthologue of CXCL1 (IL-8), is an important member of the chemokine family of pro-inflammatory chemotactic cytokines and it is also involved in systemic immunity and macrophages infiltration and activation in adipose tissue [ 45 ].…”
Section: Discussionmentioning
confidence: 99%